Polishing composition

KR103018396B1Active Publication Date: 2026-09-11FUJIMI INCORPORATED
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
KR1020210102899
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-09-23
Filing Date
2021-08-05
Publication Date
2026-09-11
Estimated Expiration
2041-08-05

Smart Images

  • Figure 112021090310785-PAT00001
    Figure 112021090310785-PAT00001
  • Figure 112021090310785-PAT00002
    Figure 112021090310785-PAT00002
  • Figure 112021090310785-PAT00003
    Figure 112021090310785-PAT00003
Patent Text Reader

Abstract

A polishing composition is provided having a sufficiently high polishing rate of silicon germanium and a sufficiently high selectivity ratio of the polishing rate of silicon germanium. The polishing composition comprises abrasive grains, an inorganic salt, and an oxidizing agent, wherein the number of silanol groups per unit surface area of ​​the abrasive grains exceeds 0 / nm² and is 2.0 / nm² or less, and the pH is 6.0 or higher.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a polishing composition. Background Technology

[0002] As a technology to reduce power consumption or improve the performance (operating characteristics) of transistors, the use of channels utilizing high-mobility materials (hereinafter also simply referred to as "high-mobility materials"), which have higher carrier mobility than Si, is being investigated. In channels fabricated using such high-mobility materials and having improved carrier transport characteristics, the drain current flowing when a specified gate voltage is applied can be increased. This provides the advantage of being able to lower the power supply voltage while obtaining a sufficiently high drain current. This advantage leads to higher performance of MOSFETs (metal oxide semiconductor field-effect transistors) at low power.

[0003] As high-mobility materials, applications are expected for group III-V compounds, group IV compounds, and graphene containing only Ge (germanium) and C (carbon). In particular, group III-V compounds containing As and group IV compounds containing Ge are being actively considered.

[0004] A channel using a high mobility material can be formed by polishing a polishing target such as silicon germanium (SiGe) having a portion containing a high mobility material (hereinafter also referred to as the high mobility material portion) and a portion containing a silicon material (hereinafter also referred to as the silicon material portion). For example, Japanese Patent Publication No. 2018-506176 (specification of U.S. Patent Application Publication No. 2017 / 0369743) discloses a polishing composition used for polishing a substrate containing germanium.

[0005] Recently, substrates containing silicon germanium and other materials such as silicon nitride (SiN) and silicon oxide (SiO2) have come into use as semiconductor substrates. With these substrates, there is a new demand to selectively polish silicon germanium relative to other materials while polishing silicon germanium at a high polishing rate. This demand has not been considered at all in the past.

[0006] Accordingly, the present invention aims to provide a polishing composition having a sufficiently high polishing rate of silicon germanium and a sufficiently high selectivity ratio of the polishing rate of silicon germanium.

[0007] To solve the aforementioned new problem, the inventors have conducted extensive research. As a result, a method comprising abrasive particles, an inorganic salt, and an oxidizing agent is produced, wherein the number of silanol groups per unit surface area of ​​the abrasive particles is 0 / nm. 2 Exceeding 2.0 pieces / nm 2 It was discovered that the above problem is solved by a polishing composition having the following and a pH of 6.0 or higher, and thus the present invention was completed. Specific details for implementing the invention

[0008] One embodiment of the present invention comprises a grit, an inorganic salt, and an oxidizing agent, wherein the number of silanol groups per unit surface area of ​​the grit is 0 / nm 2 Exceeding 2.0 pieces / nm 2 The polishing composition is one having a pH of 6.0 or higher. According to the present form of the polishing composition, the polishing speed of silicon germanium can be sufficiently increased, and the selectivity of the polishing speed of silicon germanium, that is, the selectivity of the polishing speed of silicon germanium relative to the polishing speed of other materials (e.g., silicon nitride (SiN), silicon oxide (SiO2)), can be sufficiently increased.

[0009] The mechanism by which the effects of the present invention as described above are obtained is believed to be as follows. However, the following mechanism is merely speculative and the scope of the present invention is not to be limited by it.

[0010] The number of silanol groups per unit surface area of ​​a grit is 0 / nm 2 Exceeding 2.0 pieces / nm 2 As a result, the hydrophobicity of the abrasive surface is increased. Consequently, it is believed that the polishing speed of silicon germanium oxidized by the action of an oxidizing agent can be improved.

[0011] In addition, the low number of silanol groups per unit surface area of ​​the abrasive grains reduces the amount of bound water existing between the abrasive grains and the surface of the silicon germanium film. Consequently, it is believed that the abrasive grains become more likely to come into contact with the silicon germanium film, thereby improving the polishing speed of the silicon germanium.

[0012] In addition, the inclusion of inorganic salts in the polishing composition increases the electrical conductivity of the polishing composition. As a result, the electrical double layer formed on the surface of the silicon germanium film is compressed, which is thought to enhance the action of the abrasive particles and increase the polishing speed of the silicon germanium film.

[0013] Hereinafter, embodiments related to one form of the present invention are described. The present invention is not limited to the following embodiments.

[0014] In this specification, "X to Y" indicating a range means "X or greater and Y or less." Also, unless otherwise specified, measurements of operations and physical properties, etc. are performed under conditions of room temperature (20 to 25°C) and relative humidity of 40 to 50% RH.

[0015] [Abrasive composition]

[0016] (Georip)

[0017] The polishing composition of this form has a silanol group number per unit surface area of ​​0 / nm. 2 Exceeding 2.0 pieces / nm 2It includes abrasive particles as follows. The abrasive particles have the function of mechanically polishing an object to be polished and improve the polishing speed of the object to be polished by the polishing composition.

[0018] The abrasive grains related to the present form have a number of silanol groups per unit surface area of ​​the abrasive grain (also referred to simply as "silanol group density" in this specification) of 0 / nm 2 Exceeding 2.0 pieces / nm 2 If it is less than or equal to this, it is not particularly limited. If the silanol group density of the abrasive grains is within this range, the polishing speed of silicon germanium can be sufficiently increased. The silanol group density of the abrasive grains is preferably 0.5 groups / nm. 2 2.0 or more / nm 2 It is less than or equal to, and more preferably 1.0 pieces / nm 2 2.0 or more / nm 2 It is as follows.

[0019] The number of silanol groups per unit surface area of ​​a grit can be calculated by the Sears method using neutralization titration as described by G.W. Sears in Analytical Chemistry, vol. 28, No. 12, 1956, 1982 to 1983. The number of silanol groups is calculated using the following formula.

[0020]

[0021] The number of silanol groups per unit surface area of ​​the abrasive grain can be controlled by the selection of the manufacturing method of the abrasive grain, etc.

[0022] The abrasive particles preferably contain silica, more preferably contain fumed silica or colloidal silica, and even more preferably contain colloidal silica.

[0023] The shape of the particles is not particularly limited and may be spherical or non-spherical. Specific examples of non-spherical shapes include polygonal prisms such as triangular or square prisms, cylindrical shapes, sack-shaped shapes where the center of a cylinder is bulging more than the ends, donut-shaped shapes where the center of a disc is penetrated, plate-shaped shapes, so-called cocoon-shaped shapes with a constriction in the center, so-called spherical shapes where multiple particles are integrated, so-called star candy shapes with multiple protrusions on the surface, rugby ball shapes, and various other shapes, and are not particularly limited.

[0024] When colloidal silica is used as abrasive particles, the surface of the colloidal silica may be surface modified by a silane coupling agent, etc.

[0025] As a method for surface modification of colloidal silica using a silane coupling agent, the following immobilization method may be used. For example, this can be done by the method described in “Sulfonic acid-functionalized silica through of thiol groups”, Chem. Commun. 246-247 (2003). Specifically, colloidal silica with sulfonic acid immobilized on its surface can be obtained by coupling a silane coupling agent having thiol groups, such as 3-mercaptopropyltrimethoxysilane, to colloidal silica and then oxidizing the thiol groups with hydrogen peroxide.

[0026] Alternatively, for example, it can be done by the method described in "Novel Silane Coupling Agents Containing a Photolabile 2-Nitrobenzyl Ester for Introduction of a Carboxy Group on the Surface of Silica Gel", Chemistry Letters, 3, 228-229 (2000). Specifically, colloidal silica with a carboxylic acid immobilized on its surface can be obtained by coupling a silane coupling agent containing a photoreactive 2-nitrobenzyl ester to colloidal silica and then irradiating it with light.

[0027] The above is colloidal silica having anionic groups (anionic modified colloidal silica), but colloidal silica having cationic groups (cation modified colloidal silica) may also be used. As colloidal silica having cationic groups, colloidal silica with amino groups immobilized on its surface may be used. As a method for manufacturing such colloidal silica having cationic groups, a method of immobilizing a silane coupling agent having amino groups, such as aminoethyltrimethoxysilane, aminopropyltrimethoxysilane, aminoethyltriethoxysilane, aminopropyltriethoxysilane, aminopropyldimethylethoxysilane, aminopropylmethyldiethoxysilane, and aminobutyltriethoxysilane, as described in Japanese Patent Publication No. 2005-162533, on the surface of colloidal silica may be used. By doing so, colloidal silica with amino groups immobilized on its surface can be obtained.

[0028] The average primary particle size of the abrasive grains is preferably 5 nm or larger, more preferably 10 nm or larger, and even more preferably 15 nm or larger. As the average primary particle size of the abrasive grains increases, the polishing speed of the object to be polished by the polishing composition is improved. In addition, the average primary particle size of the abrasive grains is preferably 120 nm or smaller, more preferably 80 nm or smaller, and even more preferably 50 nm or smaller. As the average primary particle size of the abrasive grains decreases, it becomes easier to obtain a surface with fewer defects by polishing using the polishing composition. The average primary particle size of the abrasive grains can be calculated, for example, based on the specific surface area (SA) of the abrasive grains calculated from the BET method, assuming that the shape of the abrasive grains is spherical. In this specification, the average primary particle size of the abrasive grains is a value measured by the method described in the examples.

[0029] The average secondary particle size of the abrasive grain is preferably 30 nm or larger, more preferably 40 nm or larger, and even more preferably 50 nm or larger. As the average secondary particle size of the abrasive grain increases, the resistance during polishing decreases, making stable polishing possible. Furthermore, the average secondary particle size of the abrasive grain is preferably 250 nm or smaller, more preferably 200 nm or smaller, even more preferably 150 nm or smaller, and particularly preferably 100 nm or smaller. As the average secondary particle size of the abrasive grain decreases, the surface area per unit mass of the abrasive grain increases, the frequency of contact with the object to be polished improves, and the polishing speed improves further. The average secondary particle size of the abrasive grain can be measured by a dynamic light scattering method, such as the laser diffraction scattering method. In this specification, the average secondary particle size of the abrasive grain adopts the value measured by the method described in the examples.

[0030] The upper limit of the aspect ratio of the abrasive particles is not particularly limited, but it is preferable that it be less than 2.0, more preferable that it be 1.8 or less, and even more preferable that it be 1.6 or less. Within this range, defects on the surface of the object to be polished can be further reduced. In addition, the aspect ratio is the average of values ​​obtained by taking the smallest rectangle circumscribing the image of the abrasive particles by a scanning electron microscope and dividing the length of the longer side of that rectangle by the length of the shorter side of the same rectangle, and can be obtained using general image analysis software. The lower limit of the aspect ratio of the abrasive particles in the polishing composition is not particularly limited, but it is preferable that it be 1.0 or higher.

[0031] In the particle size distribution obtained by the laser diffraction scattering method of abrasive particles, the lower limit of D90 / D10, which is the ratio of the particle diameter (D90) when the accumulated particle weight from the fine particle side reaches 90% of the total particle weight and the particle diameter (D10) when the total particle weight reaches 10% of the total particle weight, is not particularly limited, but it is preferable that it be 1.1 or higher, more preferable that it be 1.2 or higher, and even more preferable that it be 1.3 or higher. In addition, in the particle size distribution obtained by the laser diffraction scattering method of abrasive particles in a polishing composition, the upper limit of D90 / D10, which is the ratio of the particle diameter (D90) when the accumulated particle weight from the fine particle side reaches 90% of the total particle weight and the particle diameter (D10) when the total particle weight reaches 10% of the total particle weight, is not particularly limited, but it is preferable that it be 2.04 or lower. Within this range, defects on the surface of the object to be polished can be further reduced.

[0032] The size of the abrasive particles (average primary particle size, average secondary particle size, aspect ratio, D90 / D10, etc.) can be appropriately controlled by selecting the method of manufacturing the abrasive particles, etc.

[0033] The content (concentration) of abrasive particles in the polishing composition is not particularly limited, but it is preferable that it be 0.05 mass% or more with respect to the total mass of the polishing composition, more preferable that it be 0.1 mass% or more, and even more preferable that it be 0.3 mass% or more. In addition, the upper limit of the abrasive particle content is preferably 20 mass% or less with respect to the total mass of the polishing composition, more preferable that it be 10 mass% or less, and even more preferable that it be 5 mass% or less. That is, the silica content is preferably 0.05 mass% or more and 20 mass% or less with respect to the total mass of the polishing composition, more preferably 0.1 mass% or more and 10 mass% or less, and even more preferably 0.3 mass% or more and 5 mass% or less. Within this range, the polishing speed of the object to be polished can be improved while suppressing costs. In addition, if the polishing composition includes two or more types of abrasive particles, the content of the abrasive particles is intended to be the total amount thereof.

[0034] (Inorganic salt)

[0035] The polishing composition of this form includes an inorganic salt. This inorganic salt increases the electrical conductivity of the polishing composition and compresses the electrical double layer on the silicon germanium surface. Consequently, the action of the abrasive particles on the silicon germanium surface is enhanced, thereby increasing the polishing speed of the silicon germanium.

[0036] Examples of inorganic salts include, but are not particularly limited, salts of monovalent inorganic acids, salts of divalent inorganic acids, salts of trivalent inorganic acids, etc.

[0037] Examples of monovalent inorganic acids include hydrochloric acid, nitric acid, and nitrous acid. Examples of divalent inorganic acids include sulfuric acid, carbonic acid, sulfurous acid, thiosulfate, and phosphonic acid. Examples of trivalent inorganic acids include phosphoric acid, phosphomolybdic acid, phosphotungic acid, and vanadic acid.

[0038] Examples of these monovalent inorganic acid salts, divalent inorganic acid salts, and trivalent inorganic acid salts include lithium salts, sodium salts, potassium salts, calcium salts, magnesium salts, ammonium salts, etc.

[0039] More specific examples of inorganic salts include sodium nitrate, potassium nitrate, ammonium nitrate, magnesium nitrate, calcium nitrate, sodium nitrite, potassium nitrite, lithium carbonate, sodium carbonate, potassium carbonate, magnesium carbonate, calcium carbonate, lithium bicarbonate, sodium bicarbonate, potassium bicarbonate, ammonium carbonate, sodium bicarbonate, sodium sulfate, potassium sulfate, ammonium sulfate, calcium sulfate, magnesium sulfate, sodium sulfite, potassium sulfite, calcium sulfite, magnesium sulfite, potassium thiosulfate, lithium sulfate, magnesium sulfate, sodium thiosulfate, sodium bisulfite, ammonium sulfate, lithium hydrogen sulfate, sodium hydrogen sulfate, sodium hydrogen sulfate, potassium hydrogen sulfate, trilithium phosphate, tripotassium phosphate, trisodium phosphate, triammonium phosphate, disodium hydrogen phosphate, dipotassium hydrogen phosphate, diammonium hydrogen phosphate, sodium dihydrogen phosphate. Examples include potassium dihydrogen phosphate and ammonium dihydrogen phosphate. These inorganic salts can be used either alone or in combination of two or more.

[0040] Among these, the inorganic salt is preferably at least one selected from the group consisting of ammonium nitrate, ammonium sulfate, ammonium hydrogen sulfate, triammonium phosphate, diammonium hydrogen phosphate, and ammonium dihydrogen phosphate, more preferably selected from ammonium sulfate and triammonium phosphate, and ammonium sulfate is even more preferably selected.

[0041] The content (concentration) of inorganic salt in the polishing composition is not particularly limited, but it is preferable that it be 0.01 mass% or more with respect to the total mass of the polishing composition, more preferable that it be 0.02 mass% or more, and even more preferable that it be 0.05 mass% or more. In addition, the upper limit of the content of inorganic salt in the polishing composition used in the present invention is preferably 5 mass% or less with respect to the total mass of the polishing composition, more preferable that it be 3 mass% or less, and even more preferable that it be 1 mass% or less. If the content of inorganic salt is 0.01 mass% or more, the electric double layer of the silicon germanium film is sufficiently compressed, making it easier for abrasive particles to come into contact with the silicon germanium film, and thus the polishing speed of the silicon germanium film can be increased. If the content of inorganic salt is 5 mass% or less, the increase in electrical conductivity can be controlled, thereby compressing the electrical double layer of the abrasive grains and the film other than silicon germanium (e.g., silicon oxide film, silicon nitride film), making it difficult for the abrasive grains to come into contact with the film other than silicon germanium, and thus suppressing the increase in the polishing speed of the film other than silicon germanium. In addition, the deterioration of storage stability caused by the increase in electrical conductivity can be suppressed.

[0042] In addition, if the abrasive composition contains two or more types of inorganic salts, the content of the inorganic salts is intended to be the total amount thereof.

[0043] (Oxidizing agent)

[0044] The polishing composition of this form includes an oxidizing agent. The oxidizing agent has the function of oxidizing the surface of silicon germanium and can further improve the polishing speed of silicon germanium by the polishing composition.

[0045] Examples of oxidizing agents include hydrogen peroxide, sodium peroxide, barium peroxide, ozone water, silver(II) salts, iron(III) salts, permanganate, chromic acid, dichromate, peroxodisulfate, peroxophosphate, peroxosulfuric acid, peroxoboric acid, performic acid, peracetic acid, perbenzoic acid, perphthalic acid, hypochlorous acid, hypobromonic acid, hypoiodic acid, chloric acid, hypochlorous acid, perchloric acid, bromic acid, iodic acid, periodic acid, persulfuric acid, dichloroisocyanuric acid, and their salts. These oxidizing agents may be used alone or in combination of two or more.

[0046] Among these, it is preferable that the oxidizing agent does not contain halogen atoms, and hydrogen peroxide is more preferable.

[0047] The lower limit of the content (concentration) of the oxidizing agent in the polishing composition is preferably 0.001 mass% or more, and preferably 0.01 mass% or more. By setting the lower limit in this way, the polishing speed of silicon germanium can be further improved. In addition, the upper limit of the content of the oxidizing agent in the polishing composition is preferably 5 mass% or less, and more preferably 3 mass% or less. By setting the upper limit in this way, in addition to suppressing the material cost of the polishing composition, the burden of treating the polishing composition after use, i.e., waste liquid treatment, can be reduced. Furthermore, the risk of excessive oxidation of the surface of the object to be polished by the oxidizing agent can be reduced.

[0048] (Abrasive accelerator)

[0049] The polishing composition of this form may further include a polishing accelerator.

[0050] The polishing accelerator related to this form has the function of adsorbing to the surface of a Ge oxide film and partially modifying the Ge oxide film. The modified Ge oxide film is thought to have excellent processability and a high polishing speed, but dissolution is difficult to occur, and etching is suppressed.

[0051] It is desirable for such abrasive accelerators to have acid groups. Examples of acid groups include carboxyl groups, phosphate groups, phosphonic acid groups, sulfic acid groups, sulfonic acid groups, etc.

[0052] Specific examples of polishing accelerators include, for example, ethylenediaminetetraacetic acid, nitrilosatric acid, hydroxyethylethylenediaminetetraacetic acid, diethylenetriamineoacetic acid, triethylenetetraminehexaacetic acid, N-(2-hydroxyethyl)ethylenediamine-N,N',N'-tetraacetic acid, glycoletherdiaminetetraacetic acid, 1,3-propanediamine-N,N,N',N'-tetraacetic acid, 1,3-diamino-2-propanol-N,N,N',N'-tetraacetic acid, N-(2-hydroxyethyl)iminoacetic acid, methyl acid phosphate, ethyl acid phosphate, ethyl glycol acid phosphate, isopropyl acid phosphate, phytic acid, 1-hydroxyethylidene-1,1-diphosphonic acid, aminotri(methylenephosphonic acid), Diethylenetriaminepenta(methylenephosphonic acid), aminopoly(methylenephosphonic acid), 2-aminoethylphosphonic acid, nitrilotri(methylenephosphonic acid), N,N,N',N'-ethylenediaminetetrakis(methylenephosphonic acid), diethylenetriaminepenta(methylenephosphonic acid), ethane-1,1-diphosphonic acid, ethanehydroxy-1,1,2-triphosphonic acid, ethane-1-hydroxy-1,1-diphosphonic acid, ethane-1-hydroxy-1,1,2-triphosphonic acid, ethane-1,2-dicarboxy-1,2-diphosphonic acid, methanehydroxyphosphonic acid, 2-phosphonobutane-1,2-dicarboxylic acid, 2-phosphonobutane-1,2,4-tricarboxylic acid, α-methylphosphonosuccinic acid, Examples include N,N-di(2-hydroxyethyl)glycine, aspartic acid, glutamic acid, dicarboxymethylglutamic acid, (S,S)-ethylenediamine-N,N'-disuccinic acid, 2,3-dihydroxybenzoic acid, iminoacetic acid, ethidronic acid, mucinic acid, and salts thereof.

[0053] Polishing accelerators may be used alone or in combination of two or more types. Additionally, polishing accelerators may be synthetic products or commercially available products. Examples of commercially available polishing accelerators include Celeste PH-430, Celeste PH-540, Celeste GA, Celeste EDDS-4H, and Celeste HA (all manufactured by Celeste Co., Ltd.).

[0054] Among these polishing accelerators, from the perspective that it is possible to independently improve the processing speed of silicon germanium without changing the processing speed of other film types such as silicon oxide films or silicon nitride films, at least one selected from the group consisting of N-(2-hydroxyethyl)ethylenediamine-N,N',N'-triacetic acid, N,N,N',N'-ethylenediaminetetrakis(methylenephosphonic acid), 2-phosphonobutane-1,2,4-tricarboxylic acid, N,N-di(2-hydroxyethyl)glycine, aspartic acid, and (S,S)-ethylenediamine-N,N'-disuccinic acid is preferred, more preferably selected from N,N,N',N'-ethylenediaminetetrakis(methylenephosphonic acid) and 2-phosphonobutane-1,2,4-tricarboxylic acid, and N,N,N',N'-ethylenediaminetetrakis(methylenephosphonic acid) is further It is desirable.

[0055] The content (concentration) of the polishing accelerator in the polishing composition is not particularly limited, but it is preferable that it be 0.01 mass% or more with respect to the total mass of the polishing composition, more preferable that it be 0.05 mass% or more, and even more preferable that it be 0.08 mass% or more. In addition, the upper limit of the content of the polishing accelerator in the polishing composition is preferably 5 mass% or less with respect to the total mass of the polishing composition, more preferable that it be 3 mass% or less, and even more preferable that it be 1 mass% or less. Within this range, the polishing speed of silicon germanium can be further improved.

[0056] When a polishing composition includes two or more polishing accelerators, the content of the polishing accelerators is intended to be the total amount thereof.

[0057] (pH adjuster)

[0058] The polishing composition of this form may include a pH adjuster to make the pH 6.0 or higher.

[0059] pH adjusters are not particularly limited as long as they are compounds having a pH adjusting function, and known compounds may be used. Examples of pH adjusters include acids and alkalis.

[0060] As for the acid, either an inorganic acid or an organic acid may be used. As for the inorganic acid, there are no particular restrictions, but examples include sulfuric acid, nitric acid, boric acid, carbonic acid, hypophosphorous acid, phosphoric acid, and phosphoric acid. Examples of organic acids include, but are not particularly limited, formic acid, acetic acid, propionic acid, butyric acid, valeric acid, 2-methylbutyric acid, n-hexanoic acid, 3,3-dimethylbutyric acid, 2-ethylbutyric acid, 4-methylpentanoic acid, n-heptanoic acid, 2-methylhexanoic acid, n-octoic acid, 2-ethylhexanoic acid, benzoic acid, glycolic acid, salicylic acid, glycerinic acid, oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, maleic acid, phthalic acid, malic acid, tartaric acid, citric acid, and lactic acid, as well as carboxylic acids such as methanesulfonic acid, ethanesulfonic acid, and isethionic acid.

[0061] As for alkalis, although not particularly limited, examples include hydroxides of alkali metals such as potassium hydroxide, ammonia, quaternary ammonium salts such as tetramethylammonium and tetraethylammonium, and amines such as ethylenediamine and piperazine. Among these, ammonia is more preferred.

[0062] pH adjusters can be used alone or in combination of two or more.

[0063] The content of the pH adjuster is not particularly limited and can be appropriately adjusted so that the abrasive composition reaches the desired pH.

[0064] (Dispersed)

[0065] The abrasive composition of the present form may include a dispersion medium for dispersing each component. Examples of dispersion media include water; alcohols such as methanol, ethanol, and ethylene glycol; ketones such as acetone; or mixtures thereof. Among these, water is preferred as the dispersion medium. That is, according to a more preferred embodiment of the present invention, the dispersion medium comprises water. According to an even more preferred embodiment of the present invention, the dispersion medium comprises substantially water. Furthermore, the term "substantially" implies that a dispersion medium other than water may be included to the extent that the objective effect of the present invention can be achieved; more specifically, preferably, it comprises 90 mass% or more and 100 mass% or less of water and 0 mass% or more and 10 mass% or less of a dispersion medium other than water, and more preferably, it comprises 99 mass% or more and 100 mass% or less of water and 0 mass% or more and 1 mass% or less of a dispersion medium other than water. Most preferably, the dispersion medium is water.

[0066] From the perspective of not hindering the action of the components included in the polishing composition, water that contains as few impurities as possible is preferred as the dispersion medium; specifically, pure water, ultrapure water, or distilled water that has had impurity ions removed using an ion exchange resin and then foreign substances removed through a filter is more preferable.

[0067] (Other ingredients)

[0068] The abrasive composition of this form may additionally contain other components, such as ignition agents, preservatives, and antifungal agents, as needed. The content of other components may be appropriately set according to the purpose of their addition. The other components, namely preservatives and antifungal agents, are described below.

[0069] Examples of preservatives and antifungal agents include isothiazoline-based preservatives such as 2-methyl-4-isothiazolin-3-one, 5-chloro-2-methyl-4-isothiazolin-3-one, 1,2-benzisothiazolin-3-one, and 2-n-octyl-4-isothiazolin-3-one, parahydroxybenzoic acid esters, orthophenylphenol, and phenoxyethanol. These preservatives and antifungal agents may be used alone or in a mixture of two or more.

[0070] (pH of the abrasive composition)

[0071] The pH of the polishing composition of the present form is not particularly limited as long as it is 6.0 or higher, and can be appropriately adjusted according to the combination of abrasive particles, inorganic salts, and oxidizing agents used. The lower limit of the pH is preferably 7.0 or higher, preferably 8.0 or higher, and more preferably 9.0 or higher. The upper limit of the pH is, for example, 13.0 or lower, preferably 12.0 or lower, and more preferably 11.0 or lower. If the pH is less than 6.0, the etching reaction of silicon germanium deteriorates, and the polishing speed is significantly reduced. If the pH exceeds 13, the stability of the polishing composition cannot be maintained.

[0072] The pH of the abrasive composition can be measured by a pH meter (manufactured by Horiba Seisakusho Co., Ltd., Model No.: LAQUA).

[0073] (Method for manufacturing a polishing composition)

[0074] The method for preparing a polishing composition of the present form is not particularly limited and can be obtained, for example, by stirring and mixing abrasive particles, an inorganic salt, an oxidizing agent, and other additives as needed in a dispersion medium (e.g., water). The details of each component are as described above. Accordingly, the present invention provides a method for preparing a polishing composition comprising a process of mixing abrasive particles, an inorganic salt, and an oxidizing agent.

[0075] The temperature at which each component is mixed is not particularly limited, but it is preferably between 10°C and 40°C, and heating may be used to increase the dissolution rate. In addition, the mixing time is not particularly limited as long as uniform mixing is possible.

[0076] (use)

[0077] The polishing composition of the present form is preferably used for polishing a workpiece containing silicon germanium. It is preferable that the germanium content in the silicon germanium workpiece be 10 mass% or more.

[0078] The object to be polished in relation to the present form may include other silicon-containing materials if it contains silicon germanium. Examples of silicon-containing materials include solid silicon and silicon compounds. In addition, examples of solid silicon include single-crystal silicon, polycrystalline silicon (polysilicon, Poly-Si), amorphous silicon, etc. Examples of silicon compounds include silicon nitride (SiN), silicon oxide (SiO2), silicon carbide, etc. Low dielectric constant materials with a relative dielectric constant of 3 or less are also included as silicon-containing materials.

[0079] Examples of films containing silicon oxide include, for instance, a TEOS (Tetraethyl Orthosilicate) type silicon oxide film produced using tetraethyl orthosilicate as a precursor (hereinafter also simply referred to as a "TEOS film"), an HDP (High Density Plasma) film, a USG (Undoped Silicate Glass) film, a PSG (Phosphorus Silicate Glass) film, a BPSG (Boron-Phospho Silicate Glass) film, and an RTO (Rapid Thermal Oxidation) film.

[0080] [Polishing method and semiconductor substrate manufacturing method]

[0081] One embodiment of the present invention is a polishing method comprising a process of polishing an object to be polished using the polishing composition.

[0082] In addition, one embodiment of the present invention is a method for manufacturing a semiconductor substrate having a process of polishing the semiconductor substrate by the polishing method.

[0083] In the present type of polishing method, as a polishing device, a general polishing device may be used that has a polishing plate to which a polishing pad (polishing cloth) can be attached, and is equipped with a holder that holds and supports a substrate having a workpiece to be polished and a motor capable of changing the rotational speed.

[0084] As a polishing pad, general nonwoven fabric, polyurethane, porous fluoropolymer, etc., can be used without particular limitation. It is preferable that the polishing pad be formed with grooves into which the polishing liquid collects.

[0085] Regarding the grinding conditions, for example, the rotation speed of the grinding plate is 10 rpm (0.17 s -1 ) or more at 500rpm(8.3s -1 It is preferable that the pressure applied to the substrate having the object to be polished (polishing pressure) be 0.5 psi (3.4 kPa) or higher and 10 psi (68.9 kPa) or lower. The method of supplying the polishing composition to the polishing pad is not particularly limited, and, for example, a method of supplying continuously using a pump or the like is employed. Although there is no limit to the amount supplied, it is preferable that the surface of the polishing pad always be covered with the polishing composition related to the present invention.

[0086] After polishing is finished, the substrate is cleaned in flowing water, and water droplets attached to the substrate are removed by a spin dryer or the like, and then dried, thereby obtaining a substrate having a metal-containing layer.

[0087] The polishing composition used in the present type of polishing method may be a one-component type or a multi-component type including a two-component type. In addition, the polishing composition used in the present type of polishing method may be prepared by diluting the original solution of the polishing composition with a diluent such as water, for example, by 10 times or more.

[0088] When silicon germanium is polished by the polishing method of the present form, the polishing speed is preferably 280 Å / min. or higher, more preferably 300 Å / min. or higher, and even more preferably 400 Å / min. In addition, when silicon germanium is polished by the polishing method of the present form, the amount of etching of silicon germanium is preferably 80 Å or lower, and more preferably 60 Å or lower. In addition, the polishing speed and the amount of etching can be measured by the method described in the examples.

[0089] The polishing method of the present embodiment can be applied to a workpiece containing other materials along with silicon germanium, and in that case, the effect of having a sufficiently high ratio of the polishing speed of silicon germanium to the polishing speed of the other material (i.e., a sufficiently high selectivity ratio) can be obtained. For example, when the other material is silicon nitride, the ratio of the polishing speed of silicon germanium to the polishing speed of silicon nitride ([polishing speed of silicon germanium] / [polishing speed of silicon nitride]) is preferably 15 or higher, more preferably 20 or higher, and even more preferably 25 or higher. In addition, when the other material is silicon oxide, the ratio of the polishing speed of silicon germanium to the polishing speed of silicon oxide ([polishing speed of silicon germanium] / [polishing speed of silicon oxide]) is preferably 10 or higher, and more preferably 13 or higher.

[0090] [Example]

[0091] The present invention will be explained in more detail using the following examples and comparative examples. However, the technical scope of the present invention is not limited to the following examples. Also, unless otherwise noted, “%” and “parts” mean “mass%” and “mass parts,” respectively. Furthermore, in the following examples, unless otherwise noted, operations were performed under conditions of room temperature (20 to 25°C) and relative humidity of 40 to 50% RH.

[0092] (Example 1)

[0093] Colloidal silica as abrasive particles for the entire abrasive composition (average primary particle size 29 nm, average secondary particle size 61 nm, silanol group density 1.50 / nm) 2 0.5 mass% of (aspect ratio 1.55), 0.1 mass% of ammonium sulfate as an inorganic salt, and 0.16 mass% of hydrogen peroxide as an oxidizing agent were added. These components were stirred and mixed in pure water (mixing temperature: about 25°C, mixing time: about 10 minutes). A polishing composition was prepared by adjusting the pH to 10.4 using ammonia as a pH adjuster.

[0094] (Example 2)

[0095] A polishing composition was prepared in the same manner as in Example 1, except that ammonium sulfate was changed to triammonium phosphate.

[0096] (Example 3)

[0097] A polishing composition was prepared in the same manner as in Example 1, except that the content of colloidal silica was changed to 1.0 mass%.

[0098] (Example 4)

[0099] A polishing composition was prepared in the same manner as in Example 1, except that the content of ammonium sulfate was changed to 0.2 mass%.

[0100] (Example 5)

[0101] A polishing composition was prepared in the same manner as in Example 1, except that the pH was adjusted to 9.2.

[0102] (Example 6)

[0103] A polishing composition was prepared in the same manner as in Example 1, except that the hydrogen peroxide content was changed to 0.40 mass%.

[0104] (Example 7)

[0105] Colloidal silica as abrasive particles for the entire abrasive composition (average primary particle size 29 nm, average secondary particle size 61 nm, silanol group density 1.50 / nm) 2 A polishing composition was prepared by adding 0.5 mass% of (aspect ratio 1.55), 0.1 mass% of ammonium sulfate as an inorganic salt, 0.16 mass% of hydrogen peroxide as an oxidizing agent, and 0.1 mass% of N,N,N',N'-ethylenediaminetetrakis(methylenephosphonic acid) (EDTMP) as a polishing accelerator. These components were stirred and mixed in pure water (mixing temperature: approximately 25°C, mixing time: approximately 10 minutes). A polishing composition was prepared by adjusting the pH to 10.4 using ammonia as a pH adjuster.

[0106] (Example 8)

[0107] Colloidal silica as abrasive particles for the entire abrasive composition (average primary particle size 29 nm, average secondary particle size 61 nm, silanol group density 1.50 / nm) 2 0.5 mass% of (aspect ratio 1.55), 0.1 mass% of triammonium phosphate as an inorganic salt, 0.16 mass% of hydrogen peroxide as an oxidizing agent, and 0.1 mass% of 2-phosphonobutane-1,2,4-tricarboxylic acid (PBTC) as a polishing accelerator were added. These components were stirred and mixed in pure water (mixing temperature: about 25°C, mixing time: about 10 minutes). A polishing composition was prepared by adjusting the pH to 9.2 using ammonia as a pH adjuster.

[0108] (Comparative Example 1)

[0109] Colloidal silica as abrasive particles for the entire abrasive composition (average primary particle size 34 nm, average secondary particle size 70 nm, silanol group density 5.71 / nm) 2 0.5 mass% of aspect ratio (1.19) and 0.16 mass% of hydrogen peroxide as an oxidizing agent were added. These components were stirred and mixed in pure water (mixing temperature: about 25°C, mixing time: about 10 minutes). A polishing composition was prepared by adjusting the pH to 9.2 using ammonia as a pH adjuster.

[0110] (Comparative Example 2)

[0111] Colloidal silica as abrasive particles for the entire abrasive composition (average primary particle size 34 nm, average secondary particle size 70 nm, silanol group density 5.71 / nm) 2 A polishing composition was prepared by adding 0.5 mass% of (aspect ratio 1.19), 0.1 mass% of ammonium sulfate as an inorganic salt, and 0.16 mass% of hydrogen peroxide as an oxidizing agent. These components were stirred and mixed in pure water (mixing temperature: about 25°C, mixing time: about 10 minutes). Ammonia was used as a pH adjuster to adjust the pH to 9.2.

[0112] (Comparative Example 3)

[0113] A polishing composition was prepared in the same manner as Comparative Example 2, except that the pH was adjusted to 10.4.

[0114] (Comparative Example 4)

[0115] Colloidal silica as abrasive particles for the entire abrasive composition (average primary particle size 34 nm, average secondary particle size 70 nm, silanol group density 5.71 / nm) 20.5 mass% of aspect ratio 1.19), 0.1 mass% of potassium sulfate as an inorganic salt, and 0.16 mass% of hydrogen peroxide as an oxidizing agent were added. These components were stirred and mixed in pure water (mixing temperature: about 25°C, mixing time: about 10 minutes). A polishing composition was prepared by adjusting the pH to 10.4 using potassium hydroxide as a pH adjuster.

[0116] (Comparative Example 5)

[0117] Colloidal silica as abrasive particles for the entire abrasive composition (average primary particle size 29 nm, average secondary particle size 61 nm, silanol group density 1.50 / nm) 2 0.5 mass% of (aspect ratio 1.55) and 0.16 mass% of hydrogen peroxide as an oxidizing agent were added. These components were stirred and mixed in pure water (mixing temperature: about 25°C, mixing time: about 10 minutes). A polishing composition was prepared by adjusting the pH to 10.4 using ammonia as a pH adjuster.

[0118] (Comparative Example 6)

[0119] A polishing composition was prepared in the same manner as Comparative Example 5, except that the content of colloidal silica was changed to 4.0 mass%.

[0120] [Measurement of pH of abrasive composition]

[0121] The pH of the polishing composition (liquid temperature: 25℃) was checked using a pH meter (manufactured by Horiba Seisakusho Co., Ltd., model number: LAQUA).

[0122] [Measurement of Average Primary Particle Size and Average Secondary Particle Size]

[0123] The average primary particle size of the abrasive grains was calculated from the specific surface area of ​​the abrasive grains measured by the BET method using Micromerics’ “Flow Sorb II 2300” and the density of the abrasive grains.

[0124] The average secondary particle size of the abrasive particles was measured using the UPA-UTI151 dynamic light scattering particle size and particle size distribution device manufactured by Nikkiso Co., Ltd.

[0125] [Measurement of Silanol Group Density]

[0126] The number of silanol groups (silanol group density) per unit surface area of ​​abrasive grains was calculated by the Sears method using neutralization titration as described by G.W. Sears in Analytical Chemistry, vol. 28, No. 12, 1956, 1982 to 1983. The number of silanol groups was calculated using the following formula.

[0127]

[0128] The composition of the polishing composition prepared above is shown in Table 1.

[0129]

[0130] [Grinding Speed]

[0131] As a workpiece for polishing, the following wafer was prepared:

[0132] Silicon germanium (SiGe) wafer: A silicon wafer (300 mm, blanket wafer, manufactured by Advance Material Technology Co., Ltd.) having a silicon germanium film (Si:Ge=50:50 mass ratio) with a thickness of 1500 Å formed on its surface.

[0133] Silicon oxide (TEOS) wafer: A silicon wafer with a silicon oxide film of 10,000 Å thickness formed on its surface (300 mm, blanket wafer, manufactured by Advantec Co., Ltd.)

[0134] Silicon nitride (SiN) wafer: A silicon wafer having a silicon nitride film with a thickness of 3500 Å formed on its surface (300 mm, blanket wafer, manufactured by Advantec Co., Ltd.).

[0135] For silicon germanium wafers, silicon oxide wafers, and silicon nitride wafers, the polishing speed was determined when polished for a certain period of time under the polishing conditions shown in Table 2 below using the polishing compositions of Examples 1 to 8 and Comparative Examples 1 to 6. For the silicon germanium wafers, silicon oxide wafers, and silicon nitride wafers, a 300 mm substrate was used by couponing it into 60 mm × 60 mm.

[0136]

[0137] The polishing speed (polishing rate) was calculated by the following formula.

[0138]

[0139] The film thickness of silicon oxide and silicon nitride was determined using the Lambda Ace VM-2030 optical coherence film thickness measuring device manufactured by SCREEN Semiconductor Solutions Co., Ltd., and evaluated by dividing the difference in film thickness before and after polishing by the polishing time.

[0140] The thickness of the silicon germanium film was determined using the ZSX Primus 400 scanning fluorescence X-ray analyzer manufactured by Rigaku Co., Ltd., and evaluated by dividing the difference in film thickness before and after polishing by the polishing time.

[0141] The selectivity ratio of the polishing rate was determined by calculating the polishing rate of silicon germanium / polishing rate of silicon oxide and the polishing rate of silicon germanium / polishing rate of silicon nitride, respectively.

[0142] [Etching amount]

[0143] A silicon germanium wafer (Si:Ge=50:50 mass ratio) with dimensions of 30 mm × 30 mm was immersed in a polishing composition being rotated at 300 rpm using a stirrer for 1 hour at 43°C, and the amount of dissolution (etching amount) was calculated based on the difference in film thickness before and after immersion.

[0144] The evaluation results are shown in Table 3 below.

[0145]

[0146] As is evident from Table 3 above, the polishing composition of the example shows that the polishing speed of silicon germanium is sufficiently high compared to the polishing composition of the comparative example. In addition, it can be seen that the ratio (selectivity ratio) of the polishing speed of silicon germanium to the polishing speed of silicon oxide or silicon nitride is also sufficiently high.

[0147] This application is based on Japanese Patent Application No. 2020-158993 filed on September 23, 2020, the entirety of which is incorporated herein by reference.

Claims

Claim 1 It comprises abrasive particles, an inorganic salt, and an oxidizing agent, wherein the number of silanol groups per unit surface area of ​​the abrasive particles is 0 / nm 2 Exceeding 2.0 pieces / nm 2 A polishing composition used for polishing a workpiece comprising silicon germanium, wherein the abrasive particles are colloidal silica, the abrasive salt is at least one selected from the group consisting of ammonium sulfate, ammonium hydrogen sulfate, triammonium phosphate, diammonium hydrogen phosphate, and ammonium dihydrogen phosphate. Claim 2 A polishing composition according to claim 1, wherein the inorganic salt is at least one selected from the group consisting of ammonium sulfate and triammonium phosphate. Claim 3 A polishing composition according to claim 1 or 2, wherein the inorganic salt is ammonium sulfate. Claim 4 A polishing composition according to claim 1 or 2, wherein the oxidizing agent is hydrogen peroxide. Claim 5 A polishing composition according to claim 1 or 2, wherein the oxidizing agent does not contain a halogen atom. Claim 6 A polishing composition according to claim 1 or 2, further comprising a polishing accelerator. Claim 7 A polishing composition according to claim 6, wherein the polishing accelerator is at least one selected from the group consisting of N-(2-hydroxyethyl)ethylenediamine-N,N',N'-triacetic acid, N,N,N',N'-ethylenediaminetetrakis(methylenephosphonic acid), 2-phosphonobutane-1,2,4-tricarboxylic acid, N,N-di(2-hydroxyethyl)glycine, aspartic acid, and (S,S)-ethylenediamine-N,N'-disuccinic acid. Claim 8 A polishing method comprising a process of polishing an object to be polished using a polishing composition described in claim 1 or 2. Claim 9 A method for manufacturing a semiconductor substrate having a process of polishing the semiconductor substrate by the polishing method described in claim 8. Claim 10 delete Claim 11 delete

Citation Information

Patent Citations

  • Polishing solution for metal and chemical mechanical polishing method

    JP2008288537A

  • Aqueous dispersion for chemo-mechanical polishing and manufacturing method thereof, and chemo-mechanical polishing method

    JP2010034497A

  • Aqueous dispersion for chemical mechanical polishing and method of manufacturing the same, and chemical mechanical polishing method

    JP2010041027A

  • Polishing composition, manufacturing method thereof, polishing method, and manufacturing method of semiconductor substrate

    JP2020025066A

  • Polishing composition

    KR1020160063331A